Subclavian artery-esophageal fistula after placement of a self-expanding metal stent in a patient with esophagogastric anastomosis stenosis - Mohammadreza Seyyedmajidi; Maryam Tavassoli; Mojtaba Kiani; Jamshid Vafaeimanesh (Babol University of Medical Sciences, 2016)
Background: There have been reports on stent-related vascular erosions about patients with benign or malignant stenosis of the esophagus who received endoscopic stent insertion for palliative intention for oral intake. Case presentation: A 61-year-old woman with esophageal cancer located in the middle part of esophagus was treated with esophagectomy. Two years following the surgery, malignant stenosis recurred in the esophagogastric anastomosis. A non-covered self-expanding metal stent (10 cm length with a diameter of 18 mm at expanded state) was inserted. Three months later, a massive hematemesis with subsequent hemorrhagic shock developed from the proximal end of the stent which resulted in the final diagnosis of arterioesophageal fistula on the left subclavian artery. An endovascular repair using a stent graft for the left subclavian artery via the right common iliac artery was performed and the patient remained well until discharge. Conclusion: Increase in the treatment of esophageal strictures by stent insertion increases the risk of stent-related vascular fistula. These complications should be considered in any patients with massive upper gastrointestinal bleeding.